Investigating the psychological dependence of ethics on religion in a student population - Ali Nosrati; Massoud Azarbayjani (اخلاق وحیانی, 2021)
Purpose: the religion and morality (ethics), both have been and will be influential on human societies. what has the has engaged the scientists for a long time in this regard, is how the religion and morality relate and dependency to each other. to answer the above question, it is worth noting that the ethical philosophers have proposed four types of relationship and dependency on the ethics and religion as follows: semantical dependency; ontological dependence; epistemological Dependence; psychological dependence.The purpose of this research is the above fourth type, i.e. the study of psychological (motivational) relationship between religion and ethics.Method: all subjects were examined with two tests as, well as a religious orientation based on the Islamic religion in the Azerbaijan and on the basis of the Hyatt and Graham Ethics Foundation Questionnaire. the results of the test, after scoring, were analyzed by SPSS software and Pearson and Spearman correlation coefficient tests.findings: The results showed that there is a direct relationship between the religious attitude moral motives, that is, any amount of belief in a person becomes deeper, as much as his religious belief to convert to the faith, and the person from the cognitive and theoretical stage of religion will enter into a practical and ethical process, he will obtain a greater moral motivation and the person will find a clearer ethics existence.Conclusion: the internalized religion and religiosity play an important role in the ethical life.